The complete mitogenome of the ghost crab Ocypode ceratophthalmus (Pallas, 1772) (Crustacea: Decapoda: Ocypodidae). (3rd May 2016) - Tan, Mun Hua; Gan, Han Ming; Lee, Yin Peng; Austin, Christopher M.
Abstract: The mitochondrial genome sequence of the ghost crab, Ocypode ceratophthalmus, is documented (GenBank accession number: LN611669) in this article. This is the first mitogenome for the family Ocypodidae and the second for the order Ocypodoidea. Ocypode ceratophthalmus has a mitogenome of 15, 564 base pairs consisting of 13 protein-coding genes, two ribosomal subunit genes, 22 transfer RNAs and a non-coding AT-rich region. The base composition of the O. ceratophthalmus mitogenome is 35.78% for T, 19.36% for C, 33.73% for A and 11.13% for G, with an AT bias of 69.51% and the gene order is the typical arrangement for brachyuran crabs.